Ballet : the definitive illustrated story - Heyworth-Dunne, Victoria (DK, 2018)
Explores the history of ballet, its place in our culture of entertainment, and showcases the careers and styles of famous ballet dancers, the stories and history of production of over seventy of the most famous ballets, from "The Rite of Spring" and "The Nutcracker" to "Swan Lake."